Métodos bioestadísticos (Ediciones UC, 2013)
This text includes the class material originally prepared for the Biostatistics course of the Medicine career at the Pontificia Universidad Católica de Chile. To the successful first point of Descriptive Statistics, the others were added later and each one was enriched over time with the observations of the medical students themselves and then dozens of other students from various undergraduate and graduate careers who began to use them. . For this reason, its language is not very mathematical, but without sacrificing scientific rigor in the treatment of each subject and its great advantage is that it has been proven in its ability to transmit and teach effectively. The development of biostatistical methods follows the same path of the scientific method: a sample of the population of interest is taken, data related to the phenomenon under study are collected and the most appropriate techniques are applied to answer the research questions. This second edition has been revised and updated according to the latest versions of the statistical programs (SPSS and MINITAB), adds a new dispersion measure in the descriptive statistics chapter and complements all the topics with solved and applied exercises. Although initially it was aimed at students in health-related careers, this book will be of great use to students and researchers in any discipline who need a better understanding of the statistical methods they use on a daily basis.